Measuring Financial Performance of Student Enterpreneur’s Business - Abdul Holik; Wala Erpurini (Politeknik Ganesha Medan, 2019)
This research tries to explain the financial performance of several SMEs (Small Medium Enterprises) owned by our students. They are living examples of student that run business since in undergraduate program. The discourse to boosting SMEs cannot neglect problems related to financial performance. We obtained the result that the all financial statements showed good performance. Even though there were excess funds that the entrepreneurs not maximally used. We suspect they are doing it as a caution because they are still beginners in the business world. The businesses getting most profit are those who sell staple food substitutes. This phenomenon is because these types of foods are already familiar to most people’s tongues. While businesses that focus on drinks with specific targets, it turns out shows smaller profits and even the lowest among others. However, in total, they showed their ability as entrepreneurs, even though on a small scale.